The performance of cooperative vs capitalistic micro firms in the pandemic - Michele Costa; Flavio Delbono; Francesco Linguiti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2023)
We present a statistical analysis of the impact of the Covid-19 pandemic on Italian micro enterprises. Within the period we are examining (2012-2021), our primary focus will be on the last two years. We will show that, overall, cooperatives have been more severely affected than capitalist enterprises. The challenges faced by micro cooperatives began well before the pandemic period, but the gap with capitalist enterprises widened significantly during this time. Some concern about employment seems featuring micro cooperatives more than conventional firms. Additionally, we will concentrate on micro firms operating nationwide in two sectors that the pandemic has hit very asymmetrically and on all micro enterprises operating in the Emilia-Romagna region.
Keywords: I31; J54; L21; L25; 330; micro enterprises; cooperative firms; capitalist firms; Covid-19 pandemic